ONLINE LEARNING IN MASTER EDUCATIONAL ADMINISTRATION PROGRAM: STUDENT’S PERCEPTION - Zakaria, Zakaria (Universitas Ahmad Dahlan, 2021)
During the Covid19 epidemic that swept the world, online learning has become an essential requirement in the learning process. This research aims to describe the students of the Educational Administration Masters Study Program to online learning during the Covid-19 pandemic. This research is quantitative descriptive—the research population of the 1st and 2nd-semester students. Data collection techniques used a questionnaire—data analysis with percentage formula. The results showed that student responses to material in good categories, student responses to opportunities for discussion in good categories, student responses to the level of understanding of the material in the categories, student responses to completing assignments insufficient categories.